Serum pepsinogen I and gastrin concentrations in children positive for Helicobacter pylori. Issue 9 (September 1990) - Oderda, G; Vaira, D; Dell'Olio, D; Holton, J; Forni, M; Altare, F; Ansaldi, N
Abstract : Serum pepsinogen I, serum gastrin concentration, and inflammatory scores were measured in a population of 71 children undergoing upper gastrointestinal endoscopy for investigation of upper abdominal pain. Forty four were initially colonised with Helicobacter pylori. The indices were measured before treatment (in 71 children), one month (in 41 children), and six months (in 21 children) after stopping treatment. Before treatment there was a significant correlation between serum pepsinogen concentration, total inflammatory score, and H pylori state, but no correlation between serum gastrin concentrations and H pylori state. Similarly, the total inflammatory score and serum pepsinogen concentrations were significantly correlated. There was no such correlation in children negative for H pylori. After treatment the inflammatory score improved in those patients in whom H pylori had been eradicated. There was also a significant fall in serum pepsinogen I and serum gastrin concentration in those patients in whom H pylori had been eradicated. These results were similar to those found six months after treatment had been stopped. These findings suggest that the serum pepsinogen I concentration could be considered a useful marker for gastritis and can be used as an index of severity of gastritis in H pylori positive subjects. The measurement of serum gastrin concentrations does not give useful information.